2021
DOI: 10.1136/bmjopen-2020-047377
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy among pregnant women in a lifestyle intervention trial: protocol for an explorative study on the role of health literacy in the perinatal health service setting

Abstract: IntroductionPregnancy is a vulnerable period that affects long-term health of pregnant women and their unborn infants. Health literacy plays a crucial role in promoting healthy behaviour and thereby maintaining good health. This study explores the role of health literacy in the GeMuKi (acronym for ‘Gemeinsam Gesund: Vorsorge plus für Mutter und Kind’—Strengthening health promotion: enhanced check-up visits for mother and child) Project. It will assess the ability of the GeMuKi lifestyle intervention to positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…The questionnaire was developed as part of the GeMuKi (acronym for ‘Gemeinsam Gesund: Vorsorge plus für Mutter und Kind’—Strengthening health promotion: enhanced check-up visits for mother and child) project, the host trial, which provides counselling on lifestyle topics in addition to regular antenatal care. Details on the project and its design can be found elsewhere [ 31 , 32 ]. According to the definition of health literacy provided by Sorensen et al (2012), knowledge is a contributing factor to health literacy [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was developed as part of the GeMuKi (acronym for ‘Gemeinsam Gesund: Vorsorge plus für Mutter und Kind’—Strengthening health promotion: enhanced check-up visits for mother and child) project, the host trial, which provides counselling on lifestyle topics in addition to regular antenatal care. Details on the project and its design can be found elsewhere [ 31 , 32 ]. According to the definition of health literacy provided by Sorensen et al (2012), knowledge is a contributing factor to health literacy [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire development process resulted in eight questions in total, which can be answered on a ‘Yes/No/Don’t know’ scale [ 31 ]. Table 1 provides an overview of the items that make up the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Testing of health-promoting interventions, delivered in the absence of relationship-based care, has been proposed to improve perinatal outcomes. 57 While health promotion is an important part of quality maternity care, the provision of motivational counselling around social risk factors does not necessarily translate into women acting on advice. A trusting provider-woman relationship is foundational to pregnant women's willingness and ability to engage.…”
Section: Relationship-based Carementioning
confidence: 99%
“…After each counseling session, the participants received a reminder (push notification) of their lifestyle goals in their GeMuKi-Assist app. Further details on the GeMuKi trial and the GeMuKi intervention can be found elsewhere [33,34,42]. The GeMuKi trial was designed as a hybrid effectivenessimplementation trial, meaning that data on effectiveness and implementation were collected simultaneously [43].…”
Section: Backrgound Of This Study: the Gemuki Interventionmentioning
confidence: 99%